Jangha (wall) of the Garbhagriha of the Hazareshwar Temple - Temples of India Project Team (Jio Institute, 2024)
The jangha (wall) of the garbhagriha (sanctum sanctorum) of the Hazareshwar Temple is adorned with sculptures depicting the trinity within bhadra (central offset) niches. On the southern bhadra of the jangha, Nataraja is depicted. Nataraja is portrayed in an urdhvajanu (with raised knees) posture, holding various weapons and attributes, including a sarpa (serpant), a damaru (double-headed drum), and a pointed weapon, possibly a shula or a trishula (trident). His frontal right hand is raised near his face, while in his left hand, he holds a khatvanga (staff with a skull), with the other left hand being damaged. Using his front left hand, he makes the gajahasta (elephant trunk gesture).